A Preliminary Study of Anti‐TNFα Therapy for Symptomatic Dolichoectatic Vertebrobasilar Aneurysms - Michael Travis Caton; Kazim Narsinh; Woody Han; Ramani Chaganti; Jonathan Graf; Cathra Halabi; Ethan Winkler; Daniel L. Cooke (Stroke: Vascular and Interventional Neurology, 2024)
Background Dolichoectatic vertebrobasilar aneurysms (DVBAs) carry high morbidity, and treatment options are limited. The tumor necrosis factor α signaling cascade is implicated in DVBA growth and rupture, but the role of anti–tumor necrosis factor α therapy in DVBA has not been studied. Methods A retrospective, case–control study of DVBA at a single institution was performed. Two patients with DVBA were treated with infliximab (tumor necrosis factor α inhibitor) as part of routine therapy for rheumatoid arthritis. Three additional patients diagnosed with DVBA were studied as a control group. Routine brain magnetic resonance imaging/magnetic resonance angiography were measured by 2 blinded neuroradiologists to assess DVBA growth. Baseline comorbidities and clinical outcomes were assessed by chart review. Results The groups were similar with respect to baseline characteristics, and all patients were symptomatic at the time of DVBA diagnosis. One patient who started infliximab during the study period showed a reversal in DVBA growth rate trajectory, with a relative decrease in growth rate by 37% (0.49–0.18 mm2/day). Mean interval DVBA growth rates were lower during infliximab therapy than during noninfliximab observation intervals (0.13 versus 0.50 mm2/day; P = 0.09). Two patients in the control group died during the study period and 1 had a poor outcome (modified Rankin scale = 4). Both patients in the infliximab group had unchanged functional status (modified Rankin scale = 1) and no adverse events related to infliximab. Conclusion This study presents the first investigation of anti–tumor necrosis factor α therapy for DVBA. Infliximab was associated with low and decreasing DVBA growth trajectories with no treatment‐related adverse events. The effect of infliximab on clinical outcomes remains uncertain.